No campo dos problemas alimentares: uma técnica de tratamento psicanalítica - Mennucci, Luciana Estefno Saddi (2007)
In this dissertation I proceeded from the certification of the difficulty imposed by the standard psychoanalytic practice in the treatment of patients with feeding problems, to obtain positive results in the patient s relationship with his or her feeding, which would oblige me to introduce changes to the technique to the treatment of these patients. I sought, therefore, to study the field of feeding and the consequent feeding problems, which permitted me to enter some of the rules constituting this field such as: the social conditions of the production of symptoms, the diet mentality, the psychomechanics and the psychodynamics of feeding. Another route followed was of a search for legitimization in the changes of technique by penetrating the difference between techniques and psychoanalytic method. Maintaining in the background the studies of Susan Orbach, I took as a hypothesis that the diet mentality is a cause for great part of feeding problems and not their cure. I had to sustain myself in systematic readings about psychoanalysis, gastronomy and anthropology of feeding, as well as proceeding to the systematic study of the Multiple Fields Theory in the thematic of the psychoanalysis of the quotidian. Thus, in the course of this dissertation it became increasingly clearer that, as some of the rules of the field were revealed, specifically of the diet mentality, the route that favors an autonomy of feeding possible to the patient could be reached by the utilization of an active technique capable of touching the pure act regime that conforms the diet mentality. In this way, I could also organize the results of the reflection about my clinical work and in the conclusion that the diet mentality is both cause and consequence of a great part of feeding problems. It alienates the man of the contemporary world from the vital signs of feeding. To this man, the act of feeding, regulated by the pure act regime, ceases to be a personal decision, becomes imposed from the outside and turns into the meaning that would previously be attributed by thought